KULON PROGO AS THE GATEWAY TO DIY: A REVIEW OF SPATIAL PLANNING AND INVESTMENT LAW - Vicki Dwi Purnomo; Mashari (CV. RADJA PUBLIKA, 2025)
Kulon Progo, as the western region of the Special Region of Yogyakarta (DIY), now holds a strategic role after the operation of Yogyakarta International Airport (YIA) in Temon District. This change makes Kulon Progo the main gateway for the flow of goods, people, and capital to DIY. This article examines the legal aspects of spatial planning and investment in supporting this transformation. From the perspective of spatial planning law, the suitability of development with the Kulon Progo Regency RTRW and the challenges of synchronization between levels of spatial planning policies were discussed. Meanwhile, from the investment side, legal opportunities and obstacles in encouraging investment are analyzed, including risk-based licensing through OSS and regulatory support from the Job Creation Law. It was found that investment opportunities in the tourism, industry, and logistics sectors are quite large, but are still faced with issues of land legality, delays in RDTR, and community involvement. This study recommends accelerating digital RDTR, strengthening inter-agency coordination, and empowering local communities in the investment process. This study emphasizes the importance of certainty of spatial planning law and inclusive investment as the main requirements for sustainable development in Kulon Progo as the new gateway to DIY.